OP06 Maternal obesity programs offspring innate immune dysregulation in non-alcoholic fatty liver disease. (6th September 2011) - Mouralidarane, A; Soeda, J; Samuelsson, Anne-Maj; Taylor, P; Poston, L; Oben, J A
Abstract : Introduction: Obesity induced, non-alcoholic fatty liver disease (NAFLD), is the major cause of chronic liver dysfunction. In tandem, obesity and NAFLD rates in reproductive age women are rising. We have previously reported increased susceptibility to NAFLD in offspring exposed to maternal obesity via programming. Aim: Our aim is to investigate the effects of maternal obesity on hepatic innate immune function in a more physiologically relevant model of NAFLD. Method: Female mice were fed standard or obesogenic chow, before, throughout pregnancy and in lactation. Offspring were then weaned onto either standard or obesogenic chow and studied at 3, 6 and 12 months. Read-outs included biochemical and histological indicators of NAFLD and fibrosis, hepatic triglycerides, gene expression analysis of pro-fibrotic pathways, FACS analysis of liver innate immune cells and flow cytometric detection of ROS. Results: Offspring only exposed to a post-weaning hyper-calorific diet (Group 2) exhibited raised leptin, ALT and hepatic triglyceride content compared to controls (Group 1) (p<0.001). Moreover, hepatic gene expression of injury and fibrogenic markers were increased (Abstract OP06 table 1, p<0.01). As expected, a more robust phenotype was observed at 12 compared to 3 months. Additionally, offspring exposed to maternal obesity plus a post-weaning hyper-calorific diet (Group 3), displayed a more profound NAFLD phenotype with development of fibrosis and a NAFLD Activity Score >5. Mechanistically, we observed increased Kupffer cell numbers with impaired phagocytic function and raised ROS production, alongside reduced NKT cell numbers, in Group 3 compared to Group 1 (p<0.01). Conclusion: Maternal obesity programs development of offspring NAFLD with progression to fibrosis in the context of a post-weaning hyper-calorific diet. Innate immune dysfunction may be responsible for the observed programmed phenotype.